2013
DOI: 10.1186/1750-1172-8-53
|View full text |Cite
|
Sign up to set email alerts
|

Serum KL-6 is a predictor of outcome in pulmonary alveolar proteinosis

Abstract: BackgroundPulmonary alveolar proteinosis (PAP) is a rare disorder characterised by abundant alveolar accumulation of surfactant lipoproteins. Serum levels of KL-6, high molecular weight human MUC1 mucin, are increased in the majority of patients with PAP. The prognostic significance of KL-6 in PAP is still unknown. Aim of the study was to evaluate whether serum KL-6 levels correlate with the outcome of the disease.Patients and methodsFrom 2006 to 2012, we prospectively studied 33 patients with primary autoimmu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
28
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 33 publications
7
28
0
4
Order By: Relevance
“…marker for not only the disease activity of pulmonary fibrosis (Kohno et al 1989), but also for the monitoring of autoimmune PAP (Inoue et al 2006;Lin et al 2008;Bonella et al 2013). In our case, at the time of the diagnosis of sarcoidosis and systemic sclerosis, the chest CT scan, BAL, and trans-bronchial lung biopsy could not show the existence of autoimmune PAP; however, serum KL-6 and anti-GM-CSF antibodies levels were already highly elevated.…”
Section: Discussionmentioning
confidence: 99%
“…marker for not only the disease activity of pulmonary fibrosis (Kohno et al 1989), but also for the monitoring of autoimmune PAP (Inoue et al 2006;Lin et al 2008;Bonella et al 2013). In our case, at the time of the diagnosis of sarcoidosis and systemic sclerosis, the chest CT scan, BAL, and trans-bronchial lung biopsy could not show the existence of autoimmune PAP; however, serum KL-6 and anti-GM-CSF antibodies levels were already highly elevated.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, similar methods as described in previous studies (4,5) were used to compare the serum KL-6 levels of PAP patients of different ethnicities. We found that the mean serum KL-6 level of Chinese PAP patients was significantly higher than that of German PAP patients but close to that of Japanese PAP patients, when there was no significant difference in disease severity.…”
Section: Discussionmentioning
confidence: 99%
“…Bonella et al (5) have reported the levels of KL-6 in German Caucasian PAP patients. We found that the serum KL-6 level was significantly higher in Chinese patients with PAP than in German patients (Chinese group: 8,248±9,544 U/mL, German group: 2,049±1,893 U/mL, P<0.001; Table 4), despite the fact that similar methods were used to estimate the KL-6 levels; no significant differences in disease severity were observed [PaO 2 , P(A-a)O 2 , FVC, DLCO, and LDH levels].…”
Section: Correlation Between Initial Serum Kl-6 Level and The Need Fomentioning
confidence: 99%
See 2 more Smart Citations